Pollen-spóra interakció vizsgálata Botrytis cinerea kórokozón: egy új megközelítés előzetes eredményei - Kocsis, Ivett; Petróczy, Marietta; Markó, Gábor (GEORGIKON FOR AGRICULTURE, 2023)
There is little attention on the spore-pollen interaction, especially their background mechanisms, which microbial communications might partially explain. In this pilot study in Botrytis cinerea, we will show some first primary results, such as methodological validation and the role of some influencing factors. The preliminary results suggested valid methodological background to measure the initial growth of conidia development. Furthermore, we obtained a significant difference for the type of extract, which has a detectable time- and concentration-dependent effect. Summarizing, these results may indicate that the development of the pathogenic conidia of B. cinerea is influenced by certain regulatory molecules, which may have an analogous biological effect on the stimulatory compounds found in plant pollens.